SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/123875-ms
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hydrogen Sulphide in the Buzzard Field

Abstract: The Buzzard field, discovered in 2001, is an Upper Jurassic turbidite reservoir lying in the outer Moray Firth of the North Sea. It has an estimated STOIIP in excess of 1 Billion STB. During the appraisal drilling the fluid properties were found to be generally similar across the field with the exception of the H2S, CO2 and Mercaptan levels. During initial development drilling, using improved measurement techniques, the H2S levels were found to vary more than originally predicted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…6), found H 2 S levels three times greater than expected based on appraisal well predictions. Subsequent wells throughout the field demonstrated that the H 2 S distribution varied significantly over short distances (Beilby et al 2009). As a result, a solution for handling of higher H 2 S levels later in field life was required and the decision to install a fourth platform to handle the fluids was made.…”
Section: Pre-development Drilling Resultsmentioning
confidence: 99%
“…6), found H 2 S levels three times greater than expected based on appraisal well predictions. Subsequent wells throughout the field demonstrated that the H 2 S distribution varied significantly over short distances (Beilby et al 2009). As a result, a solution for handling of higher H 2 S levels later in field life was required and the decision to install a fourth platform to handle the fluids was made.…”
Section: Pre-development Drilling Resultsmentioning
confidence: 99%
“…Mercaptans have been reported to exacerbate high-temperature corrosion in crude and condensate distillation units . Mercaptans are also well known to reduce the fiscal value of gas and crude oil if present in sufficiently high concentrations …”
Section: Introductionmentioning
confidence: 99%
“…As, for example, biochemical sulfate reduction (BSR) needs sulfate and sulfate-reducing bacteria in environments with temperatures lower than ≈ 60 to 80 °C 3 , thermal cracking of kerogen (especially type II-S), magmatic sources and possibly thermal alteration of oils 4,5,6 . Because H 2 S is a powerful poison and has great capacity for increasing corrosion, its presence can bring significant health and economic impacts for petroleum exploration and production.…”
Section: Introductionmentioning
confidence: 99%